A Case Of Pancreatic Hamartoma Mimicking Malignancy: An Uncommon Pitfall. (28th October 2020) - Dasaraju, S; Liu, S; Kelly, R; Mneimneh, W
Abstract: Casestudy: Hamartomas are benign, disordered, tumor-like growth of cellular constituents resembling the tissue of its origin. Hamartomas are usually seen in lung, heart, kidney and spleen. Pancreatic hamartomas (PH) are extremely rare, accounting for <1% of all hamartomas. PH occurs at any age (median: 50 years) without gender predilection. PH presents as single or multiple, solid and/or cystic mass composed of exocrine tissues. Admixed neuroendocrine cells may be seen, but well-formed islets are unusual. PH stroma is typically positive for CD34 by immunohistochemistry. We present a case of a PH resected for the clinical suspicion of malignancy, with the final diagnosis established postoperatively. The case is that of a 74-year-old male with an incidental 2.3 x 1.7 x 1.1 cm hyperenhancing solid mass of the pancreatic uncinate process, found during anemia workup. The radiologic appearance was suspicious for a neuroendocrine tumor. Biopsy of the mass showed benign-appearing pancreatic ductal and acinar tissue. Given the clinical suspicion of malignancy, the patient elected to undergo a pancreaticoduodenectomy. Macroscopically the mass was well-circumscribed with solid, tan-white, firm cut surface. Microscopic examination revealed well- circumscribed proliferation of disorderly-arranged, well-differentiated, bland exocrine pancreatic tissue. Chromogranin, synaptophysin and CD56 immunostains did not highlight significant neuroendocrine component. Ki-67 proliferation index was low (1%). CD34 and CD117 immunostains were negative in the stroma. The findings were consistent with PH. Conclusion: PH may mimic a malignant process of the pancreas. The preoperative diagnosis of PH is extremely challenging due to the lack of characteristic clinical and radiological features, therefore, the diagnosis of PH is often made on resection specimen. CD34 immunostain is not always helpful for the diagnosis as it may be negative in PH stroma. Although extremely rare, pancreatic hamartoma should be considered in the differential diagnosis of a pancreatic tumor.